Engendering Philippine Mental Health - Reyes, Marita V. T.; Reyes, Jr., Baltazar V. (Review of Women's Studies, 2005)
This presentation evolved from Marita V. Reyes' involvement in gender sensitivity and mainstreaming workshops in the past six years and Baltazar V. Reyes' participation in the crafting of a National Mental Health Program in the late 1980s. It aims to bring about a better understanding of the relationship between gender and mental health and thence generate advocacy in gender sensitivity among mental health professionals and gender responsiveness in mental health institutions and programs. The ultimate goal is gender equality in mental health care through gender equitable policies and programs.